Optimization of quantitative reverse transcription PCR method for analysis of weakly expressed genes in crops based on rapeseed - Moebes, Michael; Kuhlmann, Heike; Demidov, Dmitri; Lermontova, Inna (Frontiers in Plant Science, 2022)
Rapeseed (Brassica napus) is an allopolyploid hybrid (AACC genome) of turnip rape (B. rapa, genome: AA) and vegetable cabbage (B. oleraceae, genome: CC). Rapeseed oil is one of the main vegetable oils used worldwide for food and other technical purposes. Therefore, breeding companies worldwide are interested in developing rapeseed varieties with high yields and increased adaptation to harsh climatic conditions such as heat and prolonged drought. One approach to studying the mechanism of the epigenetically regulated stress response is to analyse the transcriptional changes it causes. In addition, comparing the expression of certain genes between stress- and non-stress-tolerant varieties will help guide breeding in the desired direction. Quantitative reverse transcription PCR (RT-qPCR) has been intensively used for gene expression analysis for several decades. However, the transfer of this method from model plants to crop species has several limitations due to the high accumulation of secondary metabolites, the higher water content in some tissues and therefore problems with their grinding and other factors. For allopolyploid rapeseed, the presence of two genomes, often with different levels of expression of homeologous genes, must also be considered. In this study, we describe the optimisation of transcriptional RT-qPCR analysis of low-expression epigenetic genes in rapeseed, using Kinetochore Null2 (KNL2), a regulator of kinetochore complex assembly, as an example. We demonstrated that a combination of various factors, such as tissue homogenisation and RNA extraction with TRIzol, synthesis of cDNA with gene-specific primers, and RT-qPCR in white plates, significantly increased the sensitivity of RT-qPCR for the detection of BnKNL2A and BnKNL2C gene expression.